LoRa for multihop communication in internet of underground things under fading environments - Irfana Ilyas Jameela Manzil; Ruhul Amin Khalil; Nasir Saeed (Internet of Things and Cyber-Physical Systems)
This paper investigates the suitability of LoRa wireless technology for reliable underground-to-aboveground communication in the context of sustainable agricultural monitoring. We comprehensively analyze LoRa's performance in single-hop and multi-hop scenarios, considering complex environmental conditions and path loss. Mathematical expressions for the bit error rate (BER) are derived under both additive white Gaussian noise (AWGN) and Rayleigh fading, including multi-hop networks with decode-and-forward relays. Simulations under realistic Rayleigh fading scenarios validate our theoretical models. Our findings demonstrate that multi-hop LoRa networks significantly outperform single-hop systems in challenging underground environments, underscoring LoRa's potential for enhancing sustainability in various subterranean Internet of Underground Things (IoUT) agricultural applications.